Analysis of the Socioeconomic Characteristics of Non-Cash Food Assistance (BPNT) Recipients in the Agricultural Sector in Indonesia - Nur, Alam; Nazer, M.; Putra, Febriandi Prima (Andalasian Livestock, 2026)
The non-cash food assistance (BPNT) program in Indonesia is designed to reduce poverty and improve welfare by providing non-cash food assistance. In the agricultural sector, where many rural households depend on farming activities as their primary source of livelihood, this program needs to support vulnerable communities. The program also contributes to the achievement of SDGs 1 (no poverty) and 2 (zero hunger), which aim to reduce poverty and ensure food security. However, the implementation of this program is often affected by various factors that can lead to biases in the targeting and distribution of assistance. This study explores the socioeconomic characteristics of BPNT recipients in the agricultural sector and identifies potential biases in program implementation. The data used include various socioeconomic variables, such as education level, employment status, home ownership, housing infrastructure conditions, sanitation facilities, lighting sources, and food insecurity. The analysis shows that BPNT recipients often come from households whose heads have lower educational attainment, unstable employment conditions, or do not own their homes. Inadequate housing conditions and limited sanitation facilities are also significantly associated with receiving assistance. These findings indicate that the BPNT program still faces challenges in achieving appropriate and effective targeting. This study proposes several recommendations for improved implementation, including improved targeting mechanisms, periodic evaluations, and policy adjustments to minimize bias. Thus, BPNT can be better targeted in addressing the food needs of the most vulnerable communities while supporting the achievement of sustainable development goals.